The European Union and the South : relations with developing countries - Lister, Marjorie, 1955- (Routledge/University Association for Contemporary European Studies series., 1997)
This book presents an up-to-date, scholarly analysis of the foreign and development policy dilemmas facing Europe today. It will be essential reading for students of development policy, external relations and international affairs.